Requirements for Privatization of Iran Pro League Football Clubs - Hemati-Nejad Mehrali; Goharrostami Hamid-Reza; Sajjad Hosseini Seyyed (Physical Education of Students, 2017)
Urpose : The purpose of this research was to determine the requirements for privatization of Iran Pro League (IPL) football clubs. Methods: A questionnaire was developed and distributed among a sample of IPL coaches, executives (senior executives from the Ministry of Youth Affairs and Sports and the Privatization Organization), and faculty members (public and private universities). Descriptive statistics and Kruskal-Wallis test were used for data analysis. Besides, AHP was used in Expert Choice software to weight and rank the items. Results: The results showed that the most important factors were fighting corruption and rent-seeking during and after biddings (political), improving public perception of privatization of football clubs (sociocultural), increasing revenues from ticket sales (economic), transparency in laws regarding football club privatization (legal), and the changing structure and role of the government from exclusive ownership to oversight (structural). Conclusion: Given the results of this research, the most important requirements for privatization of IPL football clubs include offering television broadcast rights, advertisement rights, and ticket sale rights to the clubs, and these and other factors discussed earlier are likely to accelerate privatization of football clubs.